Consumer loyalty towards mobile phone brands. - Ong, Huichan. (2008)
This research branches out from common literature on consumer behavioural loyalty of mobile phone brands. It delved into the inclusion of need of cognition as an individual characteristic to provide a different perspective. The moderating effect of need for cognition was tested on the relationship between trust and satisfaction with both attitudinal and intentional loyalty. Results indicated that need for cognition had a negative effect on the relationship between brand satisfaction and intentional loyalty. This study was done in the context of the mobile phone users in Singapore.